Can nanosilica sol prevent oil well cement from strength retrogression under high temperature?. (30th July 2017) - Wang, Chengwen; Chen, Xin; Wei, Xiaotong; Wang, Ruihe
Highlights: Nanosilica sol (NSS) cannot improve compressive strength of cement under high temperature. NSS can react with Ca(OH)2 and generate honeycomb C3 S2 H4 . NSS improves compressive strength of cement containing 35% SF through filling effect. Abstract: Under high temperature, the compressive strength of cement will decrease with curing time, which is called strength retrogression. It is a great challenge to prevent strength retrogression, especially for cementing deep and thermal wells. In the past, cementing crew tend to improve the compressive strength of cement under high temperature by the addition of 35%–40% silica flour (SF). Nanosilica (NS) and silica flour have the same chemical composition, i.e., SiO2 . But NS possesses smaller particle size and larger specific surface area, which can have some special properties that SF does not have. In this paper, we investigated the effect of nanosilica sol (NSS) on the oil well cement under high temperature and revealed its mechanism through experiments. The results indicate that NSS can prevent cement stone from strength retrogression under high temperature, though it is unable to improve the compressive strength. With high addition, NSS can react with Ca(OH)2 (i.e., pozzolanic reaction), but the reaction product C3 S2 H4 has a honeycomb and loose structure. Besides, after adding 6–8% NSS, the compressive strength of cement containing 35% SF will be further improved. This is because the nanosilica particles are able to fill in the pores of the spatial structure formed by the cement hydration products, which makes a more compact and dense structure. This study lays a foundation for the application of nanosilica and other nanomaterials as cement additives, and also provides a new perspective for high-temperature well cementing design.